Physiological behavior of Cryptocarya aschersoniana seeds subjected to drying (Acta Scientiarum. Agronomy, 2025)
Seeds of Cryptocarya aschersoniana, as well as other species of the Lauraceae family, have frequently been reported to be sensitive to desiccation, which hinders their ex situ conservation. This study investigated the changes that occur during the drying of these seeds. Seeds harvested over 3 years were processed and dried at 20°C in boxes containing silica gel (with relative humidity ranging from 13.5 to 40%) to achieve a target water content of 40, 35, 30, 25, and 20%. For freshly harvested seeds, at each target water content, samples were taken, and germination tests were performed. Cell analyses were performed by using scanning electron and light microscopy (with reactions for starch and lipids). In addition, the sugars and lipid contents were determined. The results indicated that C. aschersoniana seeds are sensitive to desiccation and that under the conditions tested, the critical water content is approximately 30%, and the lethal water content is less than 18%. The seeds are dispersed while dormant, and this dormancy is partially overcome by partial drying. These seeds have some protection systems against desiccation, such as increased sucrose concentrations, during artificial drying; however, these systems are not efficient at protecting the seeds from damage caused by more intense desiccation. The images obtained allowed the verification of changes only at the point where the seeds were already completely unviable.